Sweden : Selected Issues. (IMF Staff Country Reports; Country Report, 2002)
This Selected Issues paper on Sweden analyzes possible adjustments to the fiscal framework that the authorities may wish to consider. The paper starts with a brief description of Sweden's fiscal framework, followed by an assessment of the framework's strengths and weaknesses. The scope for stabilization policy in Sweden is analyzed. The paper describes the Johansson commission's recommendations and puts forth alternative options. A strategy that would entail marginal adjustments to the framework is also proposed.